PEMBARUAN PEMIKIRAN HUKUM ISLAM: Studi tentang Teori Hudud Muhammad Syahrur - Mustafid, Fuad (UIN Sunan Kalijaga Yogyakarta, 2017)
In the last few decades, the awareness of the importance of reforming Islamic legal thought has been increasing. This is triggered by the fact that the existing Islamic law is considered less able to respond to various problems that arise and develop in the modern world. As a result, Islamic law is seen or deemed to be incompatible with the times. This is of course contrary to the doctrine or belief that Islam is a plenary religion that will always be in harmony with the times. This anxiety also afflicted Muhammad Syahrur, prompting him to examine carefully and deeply the teachings of Islam, especially those contained in God's revelation. From his careful and profound study of God's revelation, Syahrur succeeded in formulating a theory of legal excavation which became known as hudud theory. This theory is expected to be a means to reform in the field of Islamic law. This paper will try to study the theory hudud (nazhariyyah al-hudud) offered by Syahrur.Kata Kunci: Muhammad Syahrur, teori hudud, pembaruan pemikiran hukum Islam